The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10517-010-0845-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in the Brain of Mice Infected with Influenza A/H5N1 Virus

Abstract: Structural changes in the brain of outbred mice were studied after infection with influenza A/H5N1 strain isolated in the Novosibirsk region. High mortality was observed after intranasal infection. Examination of brain specimens revealed vasculopathies with thrombosis of the microcirculatory vessels, pericellular and perivascular edema with multifocal ischemic necrosis, hyperplasia of glial cells, caspase-dependent apoptosis of neurons caused by the cytopathic effect of the virus, and hypercytokinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Mice are also important models for human brains and frequently employed in morphometric assessments of brain pathology (among many others, Badea et al 2007;Chuang et al 2011;Johnson et al 2007;Ronald et al 2009;Sharief et al 2008;Potapova et al 2009). …”
Section: Animals and Dissectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice are also important models for human brains and frequently employed in morphometric assessments of brain pathology (among many others, Badea et al 2007;Chuang et al 2011;Johnson et al 2007;Ronald et al 2009;Sharief et al 2008;Potapova et al 2009). …”
Section: Animals and Dissectionmentioning
confidence: 99%
“…The introduction of fast virtual reconstruction techniques of mammalian brain morphology has lead to considerable advances in many fields of neuroscience, including medical research on humans (Dawe et al 2009;de Crespigny et al 2008;Grinberg et al 2008;Sun et al 2005;Yong-Hing et al 2005), model organisms (Ronald et al 2009;Saikali et al 2010;Potapova et al 2009), anthropological study (de Sousa et al 2010), and evolutionary investigations of mammalian brain size and -shape (e.g. Hakeem et al 2005;Montie et al 2007;Nieuwenhuys 2009).…”
Section: Introductionmentioning
confidence: 99%
“…By 10th d.p.i large areas of leukocyte infiltration in the cortex and local hemorrhage were also observed. In addition the neuronal nuclei had dark structures common to the cell nuclei disrupted by the virus [11]. As soon as we found some certain differences between the brain tissues of the infected and control groups we suggested that these disruptions can be related to the observed behavior signs.…”
Section: Resultsmentioning
confidence: 68%
“…We were able to observe neuropathological behavioral signs such as tremor and circular movements in mice infected with A/great crested grebe/Tyva/22/2010, a phenomenon not previously described for HPAI H5N1 viruses isolated in 2009. Affected mice were sacrificed and tissue samples were taken for morphological investigation as described by [11]. Numerous hemorrhages were detected in the internal organs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation